Cancer stem cells: Culprits in endocrine resistance and racial disparities in breast cancer outcomes. (1st March 2021) - Mavingire, Nicole; Campbell, Petreena; Wooten, Jonathan; Aja, Joyce; Davis, Melissa B.; Loaiza-Perez, Andrea; Brantley, Eileen
Abstract: Breast cancer stem cells (BCSCs) promote endocrine therapy (ET) resistance, also known as endocrine resistance in hormone receptor (HR) positive breast cancer. Endocrine resistance occurs via mechanisms that are not yet fully understood. In vitro, in vivo and clinical data suggest that signaling cascades such as Notch, hypoxia inducible factor (HIF), and integrin/Akt promote BCSC-mediated endocrine resistance. Once HR positive breast cancer patients relapse on ET, targeted therapy agents such as cyclin dependent kinase inhibitors are frequently implemented, though secondary resistance remains a threat. Here, we discuss Notch, HIF, and integrin/Akt pathway regulation of BCSC activity and potential strategies to target these pathways to counteract endocrine resistance. We also discuss a plausible link between elevated BCSC-regulatory gene levels and reduced survival observed among African American women with basal-like breast cancer which lacks HR expression. Should future studies reveal a similar link for patients with luminal breast cancer, then the use of agents that impede BCSC activity could prove highly effective in improving clinical outcomes among African American breast cancer patients. Highlights: Endocrine therapy is highly efficacious though some patients experience relapse. Breast cancer stem cells (BCSCs) contribute to endocrine resistance and relapse. BCSCs likely play a causal role in racial disparities observed in breast cancer. Targeting BCSCs is expected to improve luminal breast cancer patient outcomes.